Interpretation of Economic Hadith on Entrepreneurship and Business Strategy in Islam - Ahmad Ridwansah, Asep (Zona Law And Public Administration Indonesia, 2024)
This study examines the economic interpretation of Surah Quraish and its relationship with the principles of modern sharia economic law. Surah Quraysh emphasizes important values in business, such as perseverance, unity, good branding, and a balance between earning a living and worship. The principle of diligence and hard work reflects the importance of halal and independent business in the sharia economy, while unity supports the concept of cooperation in collective economic activities such as sharia cooperatives. Good branding is in line with the values of transparency and trust in Islamic business. The balance between worship and business reflects the principle of maqashid sharia, which is to maintain welfare while adhering to religious values. The principle of after-business tawakal also reflects risk management within the permissible limits, avoiding speculative practices that are not in accordance with the sharia economy. This article concludes that the interpretation of Surah Quraish provides an ethical foundation for modern sharia economic law, emphasizing the balance between material and spiritual goals in achieving prosperity based on Islamic teachings